Do boys benefit from male teachers in elementary school? Evidence from administrative panel data - Patrick A. Puhani (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
With girls having overtaken boys in many education indicators, the 'feminization' of elementary school teaching is causing debates about disadvantages for male students. Using administrative panel data on the universe of students, teachers and schools for a German state, I exploit within school and within teacher variation to determine teacher characteristics' effects on students' tracking outcomes. Germany tracks students at age 10 into more or less academic school types. I find hardly any effects of teacher's gender, age, pay level, qualifications, or working hours on boys' or girls' school track recommendations or school choice. Even when following students into middle school, no effects of elementary-school teacher gender on school type change or grade repetition can be detected.
Keywords: I21; J45; J71; J78; 330; education; gender; identification; fixed effects; teacher quality